Developmental changes in word recognition threshold from two to five years of age in children with different middle ear status. - Hall AJ; Munro KJ; Heron J (International Journal of Audiology, 2007)
The aims were to: (1) provide word recognition thresholds (WRTs) at 31, 43, and 61 months of age; (2) investigate developmental changes over time; (3) investigate the relationship between OME and WRT, and (4) investigate the relationship between WRT and hearing thresholds. Around 1000 children were tested longitudinally as part of the ALSPAC study, using an adaptive measure of word recognition in quiet. Mean WRTs were 28, 23, and 23 dB (A) at 31, 43, and 61 months, respectively. Normal auditory development is associated with a mean improvement in WRT of 5 dB between age 31 and 61 months. There was a mean increase in WRT of +5 dB and +15 dB when OME was present in one and two ears, respectively. Thus, both unilateral and bilateral OME results in a detrimental effect on hearing ability for speech. Additionally, early and 'persistent' OME is associated with greater disability. However by 61 months, previous OME status was not significant. To our knowledge, this is the largest longitudinal study reporting WRT in preschool children with different middle ear status.